2020
DOI: 10.1002/ece3.6583
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing productivity of eastern wild turkeys in northeastern South Dakota

Abstract: Population growth is highly sensitive to changes in reproductive rates for many avian species. Understanding how reproductive rates are related to environmental conditions can give managers insight into factors contributing to population change. Harvest trends of eastern wild turkey in northeastern South Dakota suggest a decline in abundance. We investigated factors influencing reproductive success of this important game bird to identify potential factors contributing to the decline. We monitored nesting rate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 44 publications
(86 reference statements)
2
9
1
Order By: Relevance
“… 1 Bakner et al (2019), 2 Badyaev and Faust (1996), 3 Badyaev et al (1996), 4 Byrne and Chamberlain (2018), 5 Chamberlain et al (2012), 6 Chamberlain et al (2020), 7 Conner et al (2006), 8 Crawford et al (2021), 9 Diefenbach et al (2012), 10 Eriksen et al (2010), 11 Fuller et al (2013), 12 Hubbard et al (1999a), 13 Kane et al (2007), 14 Kilburg et al (2014), 15 Lavoie et al (2017), 16 Little et al (2014), 17 Little et al (2016), 18 Lohr et al (2020), 19 Lowrey et al (2000), 20 Miller, Leopold, and Hurst (1998), 21 Miller, Burger, et al (1998), 22 Metzler and Speake (1985), 23 Moore et al (1993), 24 Niedzielski and Bowman (2015), 25 Norman et al (2001), 26 Norman et al (2004), 27 Pack et al (1999), 28 Paisley et al (1998), 29 Petty et al (2005), 30 Pittman and Krementz (2016), 31 Porter et al (1983), 32 Pollentier et al (2014), 33 Reynolds and Swanson (2010), 34 Roberts and Porter (1998a), 35 Roberts and Porter (1998b), 36 Seiss et al (1990), 37 Thogmartin and Johnson (1999), 38 Tyl et al (2020), 39 Vangilder and Kurzejeski (1995), 40 Wright et al (1996), 41 Wood et al (2019), 42 Yeldell et al (2017). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Bakner et al (2019), 2 Badyaev and Faust (1996), 3 Badyaev et al (1996), 4 Byrne and Chamberlain (2018), 5 Chamberlain et al (2012), 6 Chamberlain et al (2020), 7 Conner et al (2006), 8 Crawford et al (2021), 9 Diefenbach et al (2012), 10 Eriksen et al (2010), 11 Fuller et al (2013), 12 Hubbard et al (1999a), 13 Kane et al (2007), 14 Kilburg et al (2014), 15 Lavoie et al (2017), 16 Little et al (2014), 17 Little et al (2016), 18 Lohr et al (2020), 19 Lowrey et al (2000), 20 Miller, Leopold, and Hurst (1998), 21 Miller, Burger, et al (1998), 22 Metzler and Speake (1985), 23 Moore et al (1993), 24 Niedzielski and Bowman (2015), 25 Norman et al (2001), 26 Norman et al (2004), 27 Pack et al (1999), 28 Paisley et al (1998), 29 Petty et al (2005), 30 Pittman and Krementz (2016), 31 Porter et al (1983), 32 Pollentier et al (2014), 33 Reynolds and Swanson (2010), 34 Roberts and Porter (1998a), 35 Roberts and Porter (1998b), 36 Seiss et al (1990), 37 Thogmartin and Johnson (1999), 38 Tyl et al (2020), 39 Vangilder and Kurzejeski (1995), 40 Wright et al (1996), 41 Wood et al (2019), 42 Yeldell et al (2017). …”
Section: Resultsmentioning
confidence: 99%
“…We also identified a critical knowledge gap regarding demographic data for the poult period and youth survival period. Only six estimates from two studies provided sufficient data on poult survival for inclusion in our model (i.e., Shields & Flake, 2006;Tyl et al, 2020), and no studies reported youth survival. As a result, our estimates of vital rate contributions to population growth should be viewed with caution, as these missing life stages are highly influential in other galliform species with similar life history strategies TA B L E 3 Amount of variation in asymptotic growth rate, λ, explained by each vital rate for second-year individuals (SY) and after-second-year (ASY) adult eastern wild turkeys, as determined by coefficient of determination (R 2 ).…”
Section: Anthropogenic Factorsmentioning
confidence: 99%
“…We used informative prior distributions based on published estimates of female wild turkey survival rates for the intercept parameter and for the slope coefficient describing the difference in log odds daily survival between adult and juvenile wild turkeys (Tyl et al 2020). We describe our procedure for deriving informative prior distributions in Appendix 1.…”
Section: Modeling Survival Probabilitymentioning
confidence: 99%
“…To allow clear comparison of differences in survival between spring and other seasons, we assumed female turkeys were not incubating during all seasonal survival calculations. We calculated survival probability across a complete incubation period by assuming it would take 28 days to incubate a successful clutch (Tyl et al 2020). Note, however, that because adults are more likely to renest than juveniles (Tyl et al 2020), adults could have spent, on average, more days incubating than juveniles.…”
mentioning
confidence: 99%
See 1 more Smart Citation